Legal Protection of Artificial Intelligence As A Copyrights - Widya Agung Kristanti; Agung Sujatmiko; Ria Setyawati; Brahmantyo Agung Wicaksono (Eduvest - Journal of Universal Studies, 2025)
In the creative economy, technology significantly enhances human productivity and creativity, prominently through Artificial Intelligence (AI), which simulates human intelligence in computing. The rapid advancement of AI raises numerous debates, particularly in the art sector, where societal opinions vary from opposing the registration of AI-generated artwork to advocating for AI's recognition as a non-person legal entity entitled to moral rights. This discourse centers around granting legal status to AI regarding its artwork and relates to the broader concept of Intellectual Property as it pertains to creators and copyright holders. Currently, Indonesia's Copyright Law Number 8 of 2014 lacks specific provisions addressing these issues, resulting in a legal vacuum. This research aims to analyze the application of copyright legal theory to AI-generated art and the legal implications for its future development and protection. Employing normative legal research, the study utilizes both conceptual and legislative approaches, applying inductive logic to draw conclusions. Findings indicate that AI should be regarded as a legal object, with the rights to its artwork attributed to legal entities possessing natural legal authority. Additionally, the use of AI in creative works aligns with the "work made for hire" doctrine. Ultimately, the study underscores the necessity for responsive and progressive legal frameworks that adapt to the evolving landscape of copyright and AI.